Communication in Parliaments: Information, Openness and Public Engagement in Brazil - Cristiane Bernardes; Isabele Mitozo (Más Poder Local, 2025)
The article reviews studies produced in Brazil on legislative media and the digital communicative processes of parliaments to advance the analysis of the communicative configuration of the country's legislative houses. It reflects on both analog media and the digitization process of Brazilian legislative institutions since the late 20th century, as well as the effect of this phenomenon on the communicative processes carried out by these institutions and the reinforcement of democratic values through these tools. The concepts of openness, transparency, and permeability to societal influence on legislative actions are important for the specialized discussion, considering the prominence of the Brazilian case in this field for over two decades.